Design and fabrication of silicone-silica nanocomposites airway stent - Morad Hasely, Zahra; Farahani, Maryam Mazraehei; Baniassadi, Majid; Chini, Farshid; Kajbafzadeh, Abdol-Mohammad; Kiani, Arda; Baghani, Moastafa (Frontiers in Materials, 2023)
Due to the COVID-19 pandemic in recent years, many patients after extubation had stenosis in all tracheal areas because of long-term intubation. Therefore, Tracheal stenosis in these Patients is benign and can be treated using silicone stents, and many patients need silicone stents during recovery. A silicone stent is an artificial support that plays a significant role in managing airway obstruction. This research aims to fabricate an optimal silicone stent reinforced with nano-silica by vacuumed injection molding. Materials Based nanocomposites are made of RTV2 silicone with 1wt%, 3wt%, and 5wt%. of hydrophilic and hydrophobic nano-silica particles. Hardness, tensile, and hydrophobicity properties have been performed for experimental characterization of the nanocomposites. The uniform distribution of nanoparticles in the silicone matrix has been confirmed using SEM images. Adding nano-silica increases Hardness and tensile strength and improves the silicone matrix's mechanical properties. Also, the addition of nanoparticles changes the hydrophobicity properties and surface roughness. Although the presence of nanoparticles improves the mechanical properties, it also reduces the transparency and increases the viscosity. Our results show that adding 1wt%. Hydrophobic Nano-silica improves nanocomposites' mechanical properties and preserves transparency and viscosity (mold-ability) for stent construction. Adding 3wt%. Hydrophilic Nano-silica improves mechanical and hydrophobic properties, but mold ability is not easy. Finally, the fabricated nanocomposites airway stents were successfully placed on the sheep trachea in the pilot animal study.